Inequality, Democracy, and Persistence: Is There a Political Kuznets Curve? - Alberto Chong (Inter-American Development Bank, Research Department, 2001)
The aim of this paper is to provide comprehensive empirical evidence on recent theories that link democracy and income inequality for the period 1960-1995. In simple cross-country regressions I find a non-monotonic link between these two variables when using ordinary least squares, instrumental variables, and Eusufzai tests. Since these results cannot be taken as true time series findings, even though recent theories that explain such a link are, I also employ recent methods applied to dynamic models on panel data. These techniques allow accounting for potential simultaneity and heterogeneity problems. Using the preferred econometric methodology, I also find support for the existence of a political Kuznets curve. Moreover, it appears that income inequality is unconditionally persistent. Results hold for two different democracy proxies and when sensitivity analysis is applied.
Keywords: 330; Einkommensverteilung; Demokratie; Schätzung; Welt